Lehre der Digitalisierung in der Rechtswissenschaft - Schmidt, Mareike; Trute, Hans-Heinrich (Recht und Digitalisierung | Digitization and the Law, 2023)
Digitalization is reshaping the world of law; this also necessitates changes in legal education. The volume is dedicated to central questions of this change: transformations in the law and its professions, essential competencies as well as teaching concepts and their curricular anchoring. It contains the contributions of a conference organized at the University of Hamburg by the Center for Legal Didactics in cooperation with the Center for Law in the Digital Transformation. The authors are experts in law and legal education from academia and practice in Germany and abroad. They address fundamental questions as well as developments in the legal profession and concrete examples from teaching. With contributions by Bettina Mlieke | Prof. DR. Nora Rzadkowski, MHE | Prof. Dr. Tilmann Repgen | Dr. Werner Schäfke-Zell | Prof. Dr. Mareike Schmidt | Prof. Dr. Margit Seckelmann | Anton Sefkow | Ri'in OLG Dr. Dagmar Synatschke | Prof. Dr. Eric Steinhauer | Dr. David Tebel | Prof. Dr. Hans-Heinrich Trute